Dedna pogodba - Scortegagna Kavčnik, Nina (Pravnik, 2013)
In the article, the author emphasizes the importance of considering the possibility of including the contract of inheritance as the third legal title for inheritance in Slovenia, which was valid here until 1955. The author presents the position of contracts of inheritance in Slovenian legislation and points out that the argument that the testator is denied the right of freedom of testing with the contract of inheritance is very relative especially in comparative law. The author of the article calls for the reintroduction of the contract of inheritance in our legal system, for which she provides constitutional reasons and practical needs. Furthermore, she advises caution and prudence, as it would first be necessary to define only the legal nature of the contract of inheritance.
Keywords: dedno pravo; dedovanje; pogodbe; Slovenia; Slovenija; Trusts and estates